Oligometastatic prostate cancer: diagnosis and preliminary results of radiation therapy - F. R. Dzhabarov; A. B. Alnikin; V. G. Tolmachev (Вестник урологии, 2020)
Prostate cancer (PCa) remains one of the most pressing problems of modern oncology, which is primarily associated with the high prevalence of this pathology. Of course, the appearance of metastases is an unfavourable factor in the course of the disease. However, PCa metastases is a very heterogeneous condition. «Oligometastatic cancer» is considered as a special disease with other properties of the tumour, i.e. as a transitional state between the localized and disseminated stage of the disease. Diagnosis of oligometastatic cancer is an extremely difficult task associated with the accurate determination of the number and localization of metastases, both hematogenous and lymphogenous, which in turn requires differentiation with regional lesions of the lymph nodes of a locally advanced tumour process. Currently, radiotracers are widely used to diagnose metastatic lymph node lesions that have high specificity for PCa, targeting a prostate-specific membrane antigen (PSMA; also known as glutamate carboxypeptidase), such as 11C-choline, 18F-fluoroethylcholine, 68Ga.9 patients with prostate cancer with the oligometastatic lesion were treated. All patients underwent external beam radiation therapy. Total focal dose on the visualized lymph collector of the affected lymph node amounted to 44.0 Gr. Total focal dose with the method of radiotherapy treatment «field in the field» on the node 70.0 Gr. In all patients, a PSA was reduced to a level below 1.0 ng/ml 6 weeks after completion of the course of radiation therapy and levelling the severity of adverse reactions. None of the treated patients showed signs of a PCa recurrence.